Methodological Approaches to Defining the Goal of Integrated Reporting of the Enterprise - Bezverkhiy, K. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The increasing demand for the integrated reporting of the enterprise calls for the need for its quality enhancement, which is conditional on proper interpretation of its essential meaning and goal. The need for the deepest possible understanding of the integrated report- ing goal calls for analysis and summing up of the existing methodological approaches to its interpretation and definition. The study’s objective is to sum up methodological approaches to defining the goals of corporate integrated reporting of the enterprise. A review of 29 literary sources published from 2013 to 2017 (reference sources, books, PhD theses and abstracts of theses, research articles and proceedings of scientific confer- ences), where issues related with interpretation and definition of the goal of integrated report- ing of the enterprise are dealt with, is made. A matrix of definitions of the goal of integrated reporting of the enterprise, found in the sample of sources over the period of the study, and a distribution of the analyzed sources by methodological approach to defining the goal of integrated reporting of the enterprise is constructed. The analysis ofpublication activity in defining the goal of integrated reporting of the enterprise in 2013-2017 shows that the high- est publication activity was in 2016. The author’s vision of the goal of integrated reporting of the enterprise is given.